2019
DOI: 10.1097/gox.0000000000002150
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Changes in a Prospective Study of 100 Patients Requesting Breast Reduction

Abstract: Background: The anthropomometry of the “ideal” breast is well described, but changes that occur with enlarged breasts are not. The aim of this study was to assess the prevalence of nipple asymmetry in the horizontal plane and changes in the inframammary fold (IMF) in patients presenting with macromastia (defined as excessive development of the mammary glands by Merriam-Webster dictionary). Methods: One hundred patients (200 breasts) presenting to the Plastic Surgery Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“… 3 They also reported IMF descent occurring with macromastia. They 3 and others 4 reported that the breast footplate migrates inferolaterally in patients with large breasts. In addition, displacement of the NAC from the breast meridian is not uncommon.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“… 3 They also reported IMF descent occurring with macromastia. They 3 and others 4 reported that the breast footplate migrates inferolaterally in patients with large breasts. In addition, displacement of the NAC from the breast meridian is not uncommon.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, displacement of the NAC from the breast meridian is not uncommon. 3 , 4 There is surprisingly little literature dealing with the displaced nipple–areola complex in breast reduction, especially when using a superomedial pedicle. Furthermore, the pathogenesis of this condition has never been described and our postulate is noted below.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations